Enteric Duplication Cyst Located at the Posterior Tongue: A Rare Case Report and Review of the Literature - Bircan Savran; Cuneyt Kucur; Cengiz Kocak; Isa Ozbay; Mehmet Huseyin Metineren; Yasin Tugrul Karakus (Case Reports in Otolaryngology)
The lingual localization of an enteric duplication is extremely rare but may present with respiratory and feeding problems that require emergency intervention. A 7-month-old boy was brought to our clinic with feeding difficulties and tongue swelling. Physical examination showed a cystic lesion located near the left side of the tongue base that caused tongue protrusion to the contralateral side. During surgery, a 3-cm diameter opaque thick-walled cyst was found to be very closely adherent to the base of tongue, which was excised in its entirety. Following surgery, the patient fed during the early postoperative period and no complications were observed other than hypersalivation. On histological examination, a cystic lesion lined with intestinal mucosa and goblet cells was found. We present the rare case of a duplication cyst of the posterior tongue, with a literature review.